Retrospective evaluation of the relationship between seasonal factors and idiopathic sudden sensorineural hearing loss - Durmuş, Kasım; Bora, Adem; Çam, Selim; Elif Altuntaş, Emine (ENT Updates, 2018)
Objective: We aimed to investigate whether climatic conditions of the region where we live and meteorological parameters had any effect on pathogenesis and prognosis of idiopathic sudden sensorineural hearing loss (ISSNHL) or not. Methods: Sixty-eight ISSHL patients, who were treated in our department, were evaluated retrospectively. Meteorological data, including monthly ambient, maximum and minimum temperatures, relative humidity, atmospheric pressure and rainfall, were obtained from the observation station of the Central Weather Bureau of Sivas. The meteorological data for 10 days before the onset of the disorder and in a period of 21 days after the beginning of the treatment were used to investigate the relationship between climatic data and ISSNHL. Siegel’s criteria were used to evaluate the treatment success. Results: The relationship between ISSNHL and seasons was observed to be statistically significant when the seasonal distributions of the cases were evaluated statistically (p<0.05; p=0.008). The change between Siegel’s criteria and season was also statistically significant (p<0.001). As recovery in hearing of cases with ISSNHL in accordance with Seigel’s criteria and meteorological parameters were evaluated, a statistically significant difference was determined in terms of weather temperature; minimum pressure, and rainfall in the period of 10 days before the treatment. However, when patients were evaluated based on meteorological variables in the period of 21 days after the treatment, there was a statistical correlation with the hearing recovery of the patients according to Siegel’s criteria only in terms of rainfall (p<0.005). Conclusion: Our study is the first one indicating that there might be a relationship between rainfall and both pathogenesis and prognosis of ISSNHL. Even though the results of the related studies in the literature varied, we concluded that the relationship between ISSNHL and temperature, pressure, rainfall, and season should not be ignored.